Mesoporous titania–ceria mixed oxide (MTCMO): a highly efficient and reusable heterogeneous nanocatalyst for one-pot synthesis of β-phosphonomalonates via a cascade Knoevenagel–phospha-Michael addition reaction. Issue 1 (1st January 2020) - Mohammed, Mohammed Salim; Bakhtiarian, Mohsen; Bahrami, Kiumars
Abstract: Mesoporous titania–ceria mixed oxide (MTCMO) was synthesised in a sol–gel method using cerium chloride and titanium isopropoxide (TTIP) as CeO2 as well as TiO2 precursors and sodium dodecyl sulphate (SDS) as a structure-directing agent and its application was evaluated in the synthesis of aromatic β-phosphonomalonate derivatives via cascade Knoevenagel–phospha-Michael addition reaction. The catalyst characterised by various techniques like FT-IR spectroscopy, XRD, SEM, EDS, TEM and N2 adsorption-desorption. Partial substitution of Ti 4+ cations with Ce 4+ improved the BET surface area because TiO2 crystallites were suppressed to be grown. Furthermore, as a consequence of charge imbalance in the obtained Ti-O-Ce solid solution, some oxygen vacancies have generated that act as Lewis base sites while cations (Ti and Ce) around the oxygen vacancies act as Lewis acid sites. Reusability up to eight consecutive runs without significant decrease in reactivity, Mild reaction conditions, environmentally benign and compatibility with various functional groups are some of the advantages of this work.